Pengembangan Kurikulum Berorientasi Pada Mutu Pendidikan - Zainudin Zainudin (Sekolah Tinggi Agama Islam al-Amin, Gersik, Kediri, Lombok Barat, NTB, 2021)
The curriculum is a tool to achieve educational goals, namely improving the quality of Indonesian people, namely humans who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens.Etymologically the word curriculum is taken from the Greek, Curere means the distance that must be traveled by runners from start to finish. While in terminology, there are differences in the meaning of curriculum. In the old sense, the curriculum is defined as a number of subject matter that must be taken and studied by students to acquire a certain amount of knowledge, which has been arranged systematically and logically.The notion of development refers to an activity that produces a